A simple linear driving actuator for robotic arm used in land-deep sea. (1st May 2022) - Zhang, Lu; Xie, Tao; He, Shaopeng; Liang, Hao; Shi, Shengjun; Shan, Xiaobiao
Highlights: A piezoelectric motor which can effectively realize linear drive in both deep sea and land environment is proposed in this paper. The driving performance and load capacity of the designed motor on the land and deep sea with different pressure (water depth) are obtained. The experimental results show that the proposed motor can work effectively in both land and deep sea environment. Abstract: The small robotic arm used for amphibious operation in land and deep sea environment is one of the research hotspots at present. Traditional motor is gradually difficult to realize the amphibious driving of small robotic arm, a piezoelectric motor, which can effectively realize linear drive in both deep sea and land environment, is proposed in this paper. The structure of the designed motor is simple with the overall size less than 60 mm × 55 mm × 5.5 mm. The operating frequencies of the designed motor on land and in underwater with different depths were obtained. Experimental tests were carried out to test the driving performance of the prototype in the land and in underwater with different pressure (water depth). The maximum driving velocity of 376 mm/s and maximum load of 2.5 N can be achieved on land, and the maximum driving velocity of 215 mm/s can be obtained in underwater with pressure as 8 MPa (depth as 800 m). This work can provide an important reference for the research on linear driver of land-deep sea underwater operation equipment.